2010
DOI: 10.1016/j.jacr.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Long Radiology Workdays Reduce Detection and Accommodation Accuracy

Abstract: Purpose: To measure diagnostic accuracy of fracture detection, visual accommodation, reading time, and subjective ratings of fatigue and visual strain before and after a day of clinical reading. Methods:Forty attending radiologists and radiology residents viewed 60 de-identified HIPAA compliant bone examinations, half with fractures, once before any clinical reading (Early) and once after a day of clinical reading (Late). Reading time was recorded. Visual accommodation (ability to maintain focus) was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(152 citation statements)
references
References 33 publications
(29 reference statements)
9
134
1
1
Order By: Relevance
“…These classification systems are based on detailed morphologic data from patients' imaging studies; they affect treatment decisions for intervention versus conservative treatment and guide decision making for surgical approach and optimal fixation interval (4,(13)(14)(15). Classification of spine fracture patterns into these sometimes complex schemes can be a time-consuming task, resulting in additional work for the radiologist in this era of commensurately increasing workloads and study complexity (16,17). An example of a complex injury classification schema is the Magerl-AO (Arbeitsgemeinschaft für Osteosynthesefragen) system, with 53 potential categories for assignment of the detected vertebral fracture pattern (18).…”
Section: Implications For Patient Care Nmentioning
confidence: 99%
“…These classification systems are based on detailed morphologic data from patients' imaging studies; they affect treatment decisions for intervention versus conservative treatment and guide decision making for surgical approach and optimal fixation interval (4,(13)(14)(15). Classification of spine fracture patterns into these sometimes complex schemes can be a time-consuming task, resulting in additional work for the radiologist in this era of commensurately increasing workloads and study complexity (16,17). An example of a complex injury classification schema is the Magerl-AO (Arbeitsgemeinschaft für Osteosynthesefragen) system, with 53 potential categories for assignment of the detected vertebral fracture pattern (18).…”
Section: Implications For Patient Care Nmentioning
confidence: 99%
“…These increasing work demands on the radiologist community have likely contributed to increased visual fatigue [29]. A number of technical factors have also been reported to contribute to visual fatigue including workstation design, monitor resolution, brightness and contrast, image refresh rates, screen flicker and glare, and working distances and angles [12].…”
Section: Evolutionary Pressures In Radiology Practice Affecting Fatiguementioning
confidence: 99%
“…After a day of image interpretation, error in visual accommodation was greater (p<0.01) and subjective fatigue ratings were higher. We concluded that after a day of clinical reading, radiologists have reduced ability to focus, increased symptoms of fatigue and oculomotor strain, and reduced ability to detect fractures [29].…”
Section: Visual Fatiguementioning
confidence: 90%